'Our Strength comes from the Land': the Hybrid Culinary Traditions of the Six Nations of Grand River in the Early Twentieth Century - Norman, Alison (Cuizine)

(untitled) (McGill University Library, 2015)
This article examines the evolution of culinary traditions among the Haudenosaunee (Iroquois) in southern Ontario into the mid-twentieth century, and particularly the diets of the Christian community in the early twentieth century. It looks at the impact of the schools (especially the Mohawk Institute residential school) and churches on the reserve, and how voluntary organizations were at the forefront of promoting an Anglo-Canadian diet in the community. It considers the role that food and cooking played in the lives of Christian Six Nations women and suggest that despite the colonial challenges they faced, these women continued to use food as a way to care for their community.